"Do Not Do Abroad What You Would Not Do at Home?": An Exploration of the Rationales for Extraterritorial Criminal Jurisdiction over a State's Nationals. (4th November 2020) - MÉGRET, FRÉDÉRIC
Abstract: Compared to universal jurisdiction, active nationality jurisdiction remains one of the least understood and written about forms of extraterritorial criminal jurisdiction. This article seeks to offer a normative account of the exercise of criminal jurisdiction by states over their nationals for crimes committed abroad such as sexual offences against minors, bribery of foreign public officials, or medical "circumvention" tourism. It highlights all of the reasons that militate against such assertions of jurisdiction as a matter of policy and law. It goes on to argue that the assertion of criminal jurisdiction over nationals for crimes committed abroad must be understood beyond its permissibility under international law as a modality that manifests the interests of the state of nationality, the territorial (host) state on occasion, the relevant individuals, and, increasingly, the international community.